Inhibitory effect and mechanism of linoleic acid sustained-release microspheres on Microcystis aeruginosa at different growth phases. (December 2018) - Ni, Lixiao; Rong, Shiyi; Gu, Guoxiu; Hu, Lingling; Wang, Peifang; Li, Danye; Yue, Feifei; Wang, Na; Wu, Hanqi; Li, Shiyin
Abstract: Environment-friendly algaecides based on allelopathy have been extensively studied to control harmful algal blooms (HABs). The inhibitory effects of linoleic acid (LA) sustained-release microspheres on different cell densities of Microcystis aeruginosa ( M. aeruginosa ) at different growth phases were studied. The results showed that the growth of M. aeruginosa could be inhibited within 4 days and the constant inhibitory rate with initial algal density of 8 × 10 5  cells∙mL −1 (exponential phase) was up to 96% compared with control. The chlorophyll-a content in the treatment group had the same change trend with the algal density and declined significantly at day 20th, which suggested that the microspheres could promote the degradation of chlorophyll-a. The activities of superoxide dismutase (SOD) and catalase (CAT) increased gradually within 5 days but then declined sharply, which indicated that LA microspheres could cause oxidative damage to M. aeruginosa during the process of inhibition and reduce the activities of antioxidant enzymes. In addition, the concentration of oxygen free radical (O2 − ) increased at day 10th and rose constantly, and the content of malodialdehyde (MDA) increased to 2.7 times as much as control at day 20th. Furthermore, the content of protein, nucleic acid and the conductivity in culture solution showed a significant rise. These results showed that algal cell membrane lipid peroxidation occurred and the membrane permeability increased, accompanied by the damage of cell membrane. To sum up, the destruction of algal cell membrane is the main mechanism of LA microspheres inhibiting algal growth.